The Interest and Motivation of Future Class Teachers at Madrasah Ibtidaiyah Towards Routine Sports and Teaching Physical Education - Fatkhur Rozi; Heny Setyawati; M.E. Winarno; Bambang Priyono (Universitas Negeri Semarang, 2023)
Physical education learning in the Pendidikan Guru Madrasah Ibtidaiyah (PGMI)/teacher education for islamic elementary school study program is carried out to prepare future madrasa class teachers who can teach physical education and have healthy living habits through sports. The purpose of this study was to analyze the interest of future elementary school teachers (students) in exercising and teaching physical education. The research design used was a survey with quantitative descriptive data analysis. The population of this study was PGMI students who took part in physical education lectures with a total of 61 students. The sample of this research was 45 students who were selected using the technique of quota sampling. The research was conducted in March 2023. The data was generated from student answers to questionnaires that had been distributed online. The results show that after receiving physical education lectures, 91% of students have interest and motivation to exercise regularly with 67% of them at least 3 times a week, and 100% of students are ready to teach physical education when they become class teachers and there is no special teacher for physical education. In addition, the results show an average score of 7, indicating high interest and motivation. On average students as future teachers for Islamic elementary schools have a high interest and motivation to exercise regularly and are ready to teach physical education after receiving physical education lectures.